Teologi Misi Holistik Berbasis Kejadian 1:28 dan Matius 28:19-20 (Jurnal Pendidikan Agama dan Teologi, 2025)
The mission of God, or Mission Dei, begins with God Himself. God is not only the source of salvation, but also the center of the mission; therefore, without God there is no mission. So, God is the source, initiator, executor, and fulfiller of His purpose. The purpose comes from the heart of God and never changes. The cultural mandate, or cultural mandate, is the first mandate given to humans. God made humans to rule over all living things, including livestock, sea animals, birds of the air, and fish in the sea and the Great Commission written in Matthew 28:19-20 tells of Jesus' mission asking everyone to go, make disciples, baptize, and teach. This study was conducted using a qualitative approach through literature study. This study concluded that by studying holistic mission theology based on Genesis 1:28 and Matthew 28:19-20, we can understand that mission is not only preaching the Word but also having the responsibility to prosper humans both physically and spiritually and can manage natural resources where they are.